2017
DOI: 10.3345/kjp.2017.60.12.385
|View full text |Cite
|
Sign up to set email alerts
|

Does anaesthesia in mothers during delivery affect bilirubin levels in their neonates?

Abstract: PurposeThis study aimed to assess whether different anesthetic techniques and oxytocin use applied during delivery affect transcutaneous bilirubin levels during the first 24 hours in neonates.MethodsA total of 1,044 neonates delivered by either caesarian section (C/S) or normal vaginal delivery (NVD) were included in the study. They were classified into 5 groups as follows: group 1: born by C/S using general anesthesia, group 2: C/S using spinal anaesthesia, group 3: C/S using general anesthesia after failed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…10,11 In a study in which newborn bilirubin levels with general anesthesia and NSVD were compared, 24-hour serum bilirubin values were found to be high, although not statistically significant. 12 El Kabbany et al 13 there is a current study reporting that maternal general anesthesia has a negative effect on newborn bilirubin. In our study, we found that the 1st hour bilirubin and 4 th hour bilirubin values in the general anesthesia group were significantly higher than the group that did not receive anesthesia (p<0.05, p=0.001).…”
Section: Discussionmentioning
confidence: 86%
“…10,11 In a study in which newborn bilirubin levels with general anesthesia and NSVD were compared, 24-hour serum bilirubin values were found to be high, although not statistically significant. 12 El Kabbany et al 13 there is a current study reporting that maternal general anesthesia has a negative effect on newborn bilirubin. In our study, we found that the 1st hour bilirubin and 4 th hour bilirubin values in the general anesthesia group were significantly higher than the group that did not receive anesthesia (p<0.05, p=0.001).…”
Section: Discussionmentioning
confidence: 86%
“…Newborns of women administered synthetic oxytocin in labour also have higher risks of jaundice, likely due to increased erythrocyte fragility [ 215 218 ]. Studies have also found that newborns of exposed women have lower levels of glutathione and markers that indicate more oxidative stress, compared to newborns of unexposed women, likely due to hypoxic effects [ 219 – 221 ].…”
Section: Discussionmentioning
confidence: 99%
“…These factors caused bilirubin accumulation and led to ABE ( 21 ). The type of delivery also affected the risk of ABE; cesarean births were more likely to develop ABE, and this may be related to anesthesia ( 22 , 23 ). In the radiomics model, the selected features were composed of the following categories: one first-order feature (Left_Skewness), two shape features (Right_SurfaceVolumeRatio and Left_Maximum2DDiameterRow), and seven texture features (Right_ RunEntropy, Left_Correlation, Right_SmallAreaLowGrayEmphasis, Right_Imc1, Right_Correlation, Left_GrayLevelNonUniformity_2, and Left_Idmn).…”
Section: Discussionmentioning
confidence: 99%